Civil Rights Under Attack by the Military - Sylvia Law (Washington University Journal of Law & Policy, 2001)
First, I will describe the issues surrounding the discrimination against gay people in a larger social and legal context. Second, I will discuss the recent changes in federal policies in relation to federal funding for universities and federal coercion to pressure universities to abandon anti-discrimination policies. Finally, I will describe the range of responses either considered or adopted in schools around the country.
Keywords: Homophobia; Universities & colleges; Federal aid; Armed Forces; United States. Dept. of Justice; Law school; Discrimination; Military law